RESEARCHES of INFLUENCE of THE FUEL TANKS DESIGN OF AIRcraft ON ACCUMULATION OF THE ELECTROSTATIC CHARGE AT REFUELLING - N. E. Syrojedov; V. G. Petuxov; F. E. Sharykin; E. G. Makhmudbekova (Научный вестник МГТУ ГА)
The article describes the results of researches of influence of fuel tanks design of aircraft on accumulation of electrostatic charge at refuelling.